Mathematical disposition of students’, teachers, and parents in distance learning: A survey - Nuhyal Ulia; Imam Kusmaryono (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study reveals (1) the mathematical dispositions of students, teachers, and parents in distance learning, and (2) factors forming the mathematical dispositions of students, teachers, and parents in distance learning. The method used in this research is a survey-based qualitative descriptive analysis. The subjects of the study were 20 elementary school students, 20 elementary school teachers, and 20 parents who have elementary school-aged children (6 to 11 years). The research data were collected through questionnaires and interviews. The results showed that the level of students' mathematical dispositions in distance learning was at a moderate level, the parents' mathematical dispositions were at a moderate level but tended to below, while the teachers' mathematical dispositions were at a high level. There are three factors that need to be considered to determine a mathematical disposition, namely the presence or absence of a mathematical disposition, its direction, and its intensity. Meanwhile, an interactive learning atmosphere, fast feedback, the use of technology, and the right content are factors in forming mathematical dispositions. This supports the proposition that the disposition (students, teachers, parents) towards mathematics learning is influenced by rules and practices in schools, teacher-student relationships, and expectations that determine the learning climate.